2019
DOI: 10.1016/j.whi.2019.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Social Service Needs of Pregnant Women Who Consider but Do Not Have Abortions

Abstract: Purpose: States have enacted an increasing number of policies restricting access to abortion. As a result, some women are unable to obtain an abortion and instead continue their pregnancies. These women may have particular needs that would bring them to the attention of public health programs. Methods: Pregnant women entering prenatal care completed a self-administered survey and structured interview at four prenatal facilities in Louisiana and Maryland (N ¼ 586). Participants reported their pregnancy intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This means that these groups are disproportionately impacted by restrictive abortion policies; they are also groups who may need additional support to be able to obtain abortions and, when not able to obtain abortions, to obtain services during their pregnancy and afterwards. In fact, our previous research has found that women who report policy-related barriers to abortion report needing services such as substance use disorder treatment [34]. Previous research underscores the importance of thinking about how to support women unable to obtain abortions, as this research indicates that denying women abortion does not resolve factors (such as problematic alcohol use or economic insecurity) that existed prior to her becoming pregnant or that led her to consider abortion in the first place [13,35].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This means that these groups are disproportionately impacted by restrictive abortion policies; they are also groups who may need additional support to be able to obtain abortions and, when not able to obtain abortions, to obtain services during their pregnancy and afterwards. In fact, our previous research has found that women who report policy-related barriers to abortion report needing services such as substance use disorder treatment [34]. Previous research underscores the importance of thinking about how to support women unable to obtain abortions, as this research indicates that denying women abortion does not resolve factors (such as problematic alcohol use or economic insecurity) that existed prior to her becoming pregnant or that led her to consider abortion in the first place [13,35].…”
Section: Discussionmentioning
confidence: 91%
“…We also aimed to: 1) Understand women's experiences considering and seeking abortions in a state with multiple versus few restrictive abortion policies; 2) Assess health & social service needs of women who consider but do not have abortions; and 3) Understand women's experience with and impacts of Pregnancy Resource Centers. We have previously published some findings related to each aim [5,8,[22][23][24]]. The analyses presented in this manuscript are a-priori components of the first aim.…”
Section: Methodsmentioning
confidence: 99%
“…It means that about 7% of all abortion requests were rejected because of gestational age of more than 19 weeks while it could be prevented. Mothers who do not receive the permission for abortion for a fetus with significant anomalies just because it is older than 19 weeks could be at risk of performing unsafe abortion (41). Lack of information about the rules and regulations concerning abortion among the prenatal caregivers such as gynecologists, midwives, and general practitioners (42,43) and also the society (44, 45) could be considered as reasons for delayed referral and therefore, their education in this matter should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…It means that about 7% of all abortion requests were rejected because of gestational age of more than 19 weeks while it could be prevented. Mothers who do not receive the permission for abortion for a fetus with signi cant anomalies just because it is older than 19 weeks could be at risk of performing unsafe abortion (41). Lack of information about the rules and regulations concerning abortion among the prenatal caregivers such as gynecologists, midwives, and general practitioners (42,43) and also the society (44,45) could be considered as reasons for delayed referral and therefore, their education in this matter should be taken into account.…”
Section: Discussionmentioning
confidence: 99%